E-Government, Information and Communications Technology Support and Paperless Environment in Nigerian Public Universities: Issues and Challenges - AbdulKareem, Abdulrazaq Kayode; Bello, Muhammed Lawan; Ishola, Abdulrasaq Ajadi; Jimoh, Lukman Adams (Journal of Technology Management and Business, 2020)
The move toward a paperless environment has become the driving force behind sustainable development and e-government usage in many public sector institutions. It is equally at the heart of the government campaign to make service delivery in public institutions cost-effective, seamless, and efficient. The universities are supposed to be at the front-line of this campaign due to their operations which involve the heavy usage of papers at huge costs. Thus, making it important for university management to provide ICT support in order to promote paperless exchange of information and presentations. It is, however, understood recently, that there are issues which surround the low usage of ICT among university management and ultimately paperless environment. The purpose of this paper, therefore, is to conceptually discuss the mode of university operations and how paperless environment can be attained. The paper highlights the cyclical order of document generation, document management and document sharing as the process in which a paperless environment can take place within both the academic and the administrative settings in the university. The paper further discusses the challenges hindering the attainment of paperless environment among which are infrastructural gap, inadequate ICT support and attitudinal challenge. It is recommended that for the smooth operation of a paperless environment, the government must bridge the infrastructure gap especially power as well as train and retrain staff on the path ICT usage.